Inhibition of P-glycoprotein mediated multidrug resistance by stemofoline derivatives - Sonthaya Umsumarng (2018)
Resistance to chemotherapy in cancer patients has been correlated to the overexpression of the ATPbinding cassette (ABC) drug transporters including P-glycoprotein (P-gp) that actively efflux chemotherapeutic drugs from cancer cells. We examined the mutidrug resistance reversing property of stemofoline derivatives in drug-resistance human cervical carcinoma (KB-V1) and human leukemic (K562/Adr) cell lines that overexpress P-gp. Didehydrostemofoline and eleven of its derivatives were synthesized and the cytotoxicity and their effect on doxorubicin, vinblastine and paclitaxel sensitivity in drug resistant (KB-V1 and K562/ Adr) and drug sensitive (KB-3-1 and K562) cell lines by a 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay were determined. We found that three out of the twelve stemofoline derivatives including OH-A1, NH-B6 and NH-D6 showed commitment efficiency to increase sensitivity to doxorubicin, vinblastine and paclitaxel in KB-V1 cells and increase sensitivity to doxorubicin, and paclitaxel in K562/Adr cells whereas the effects have not been seen in their parental sensitive cancer cell lines (KB-3-1 and K562). These results indicate that stemofoline derivatives reversed P-gp-mediated multidrug resistance in vitro, and thus could be developed as effective chemosensitizers to treat multidrug-resistant cancers. The molecular mechanism of modulation of P-gp would be further determined. © 2013 The Pharmaceutical Society of Japan.